Pengaruh Team Work Dan Beban Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pendidikan Dan Kebudayaan Kabupaten Lombok Timur - Rohmiyatun Ilmi; Syaiful Amri; Rosyia Wardani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
The purpose of this study was to examine several things, as follows: (1) the effect of team work on performance, (2) the effect of workload on performance, (3) the effect of team work and workload on performance. In this study using associative research with a population of 80 people and a sample of 80 people who are employees of the Office of Education and Culture of East Lombok Regency. The data collection technique used in this study was in the form of a statement in the form of a questionnaire. The findings showed that: (1) Team work has a significant effect on performance because it has a larger t count than t table, namely 4.212 > 1.991 with a significance value of 0.001 1.991 with a significance value of 0.001 3.12.